2009
DOI: 10.1016/j.drugalcdep.2008.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome for short-term medically supervised opioid withdrawal during a randomized, multicenter trial of buprenorphine–naloxone and clonidine in the NIDA clinical trials network drug and alcohol dependence

Abstract: Few studies in community settings have evaluated predictors, mediators, and moderators of treatment success for medically supervised opioid withdrawal treatment. This report presents new findings about these factors from a study of 344 opioid dependent men and women prospectively randomized to either buprenorphine-naloxone or clonidine in an open-label 13-day medically-supervised withdrawal study. Subjects were either inpatient or outpatient in community treatment settings; however not randomized by treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 33 publications
6
53
2
1
Order By: Relevance
“…At one study site, the rate of nicotinedependent OA patients was 96% (Figure 1). This is consistent with findings in opioid-addicted populations treated at community treatment programs (Reid et al, 2011;Ziedonis et al, 2009). …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…At one study site, the rate of nicotinedependent OA patients was 96% (Figure 1). This is consistent with findings in opioid-addicted populations treated at community treatment programs (Reid et al, 2011;Ziedonis et al, 2009). …”
Section: Discussionsupporting
confidence: 81%
“…A recent investigation in a large nonsubstance abusing population reported that active smokers treated for chronic pain were less likely to complete methadone taper (Hooten, Townsend, Bruce, & Warner, 2009). Ziedonis et al (2009) found that smoking was a predictor of negative opioid detoxification outcome in a multisite trial and argued for the need to study the impact of tobacco on opioid withdrawal. We identified an association between active smoking and opioid withdrawal and craving intensity, in combination with lower rates of detoxification completion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional large-scale, clinical trials evaluated predictors and mediators of treatment success for inpatients who received either Suboxone or clonidine. Contrary to what was hypothesized, higher rates of treatment success were observed for patients who had high baseline withdrawal scores [23]. More specifically, inpatients with high baseline withdrawal symptoms were four times more likely to achieve detoxification and sustained abstinence than inpatients with lower baseline withdrawal symptoms.…”
Section: Suboxone Treatment Versus Other Treatment Modalitiescontrasting
confidence: 50%
“…Although comparable in efficacy, buprenorphine carries a lower risk of overdose [21]. Furthermore, it is important that buprenorphine therapy is initiated at the onset of withdrawal symptoms as research indicates that inpatients without a history of substance abuse that have high baseline withdrawal scores appear to benefit the most from long-term Suboxone treatment [22,23]. An additional disadvantage of buprenorphine therapy involves its potential inefficacy in individuals who required high methadone doses prior to buprenorphine treatment.…”
Section: Suboxone Treatment Versus Other Treatment Modalitiesmentioning
confidence: 99%